2013
DOI: 10.1002/pola.26967
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of water‐soluble allyl‐functionalized oligochitosan and its modification by thiol–ene addition in water

Abstract: A novel, straightforward and versatile chemical pathway has been studied to functionalize water‐soluble chitosan oligomers. This metal‐free methodology is based on the epoxy‐amine reaction of the allyl glycidyl ether with chitosan, followed by thiol‐ene radical coupling reaction of ω‐functional mercaptans, using 4,4′‐Azobis(4‐cyanovaleric acid) as a free radical initiator. Both reactions were entirely carried out in water. In a preliminary step, chitosan depolymerization was carried out using H2O2 in an acetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…Thus, ammonium and carboxylic acid functions were introduced in two steps as shown in Scheme . Numerous papers have reported the modification of the primary amine of chitosan with epoxides in a water medium . Thus, in a first step, allyl and trimethylammonium moieties were introduced along the chitosan backbone through epoxide–amine reactions with allyl glycidyl ether (AGE) and glycidyl trimethylammonium (GTA) chloride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ammonium and carboxylic acid functions were introduced in two steps as shown in Scheme . Numerous papers have reported the modification of the primary amine of chitosan with epoxides in a water medium . Thus, in a first step, allyl and trimethylammonium moieties were introduced along the chitosan backbone through epoxide–amine reactions with allyl glycidyl ether (AGE) and glycidyl trimethylammonium (GTA) chloride.…”
Section: Resultsmentioning
confidence: 99%
“…The functionalization with glycidyl trimethylammonium chloride seems to be more difficult probably owing to the charge repulsion between quaternary ammonium moieties. The allyl‐group‐containing compound 1 (see Scheme for structure of compounds 1 and 2 ) was then functionalized with 3‐mercaptopropionic acid using a thiol‐ene addition reaction to afford compound 2 according to a procedure reported by Illy et al . 1 H NMR analysis of compound 2 demonstrated that the addition of the thiol to the allyl groups occurred in 100 % yield, with data consistent with that expected for the modified side chain groups (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…The obtained products, which self-aggregated into nanogels in PBS buffer, were subsequently crosslinked by pentaerythritol tetra(mercaptoethyl) polyoxyethylene (PEGSH) to give raspberry-like assemblies of nanogels ( Figure 18). The introduction of α,β-unsaturation could also be performed on polysaccharide Esterification [144][145][146] or etherification [145,147] reaction were capable to react with thiols at neutral pH in aqueous media. In a different approach, ene-functionalized cellulose surfaces were prepared by silylation of cellulose hydroxyls with vinyltrimethoxysilane, followed by thiol-ene click reaction under UV irradiation [152].…”
Section: Pre-functionalization Of Polysaccharide Backbone With Olefinmentioning
confidence: 99%
“…Therefore, the solubility in aqueous media, which is characteristic for the initial polymer, will not be signicantly reduced if the degree of substitution (DS) by hydrophobic moieties is not too high. 28 It is known a method for alkylation of chitosan with allyl bromide in Pr i OH in presence of large excess of alkali, 29,30 performed similarly to heterogeneous processes for allyl cellulose derivatives. The authors note the diffusively complicated type of the process due to bad swelling of chitosan both in alkali and Pr i OH.…”
Section: Introductionmentioning
confidence: 99%